Why Does Working from Home Vary across Countries and People? - Pablo Zarate; Mathias Dolls; Steven J. Davis; Nicholas Bloom; Jose Maria Barrero; Cevat Giray Aksoy (Center for Economic Studies and ifo Institute (CESifo), 2024)
We use two surveys to assess why work from home (WFH) varies so much across countries and people. A measure of cultural individualism accounts for about one-third of the cross-country variation in WFH rates. Australia, Canada, the UK, and the US score highly on individualism and WFH rates, whereas Asian countries score low on both. Other factors such as cumulative lockdown stringency, population density, industry mix, and GDP per capita also matter, but they account for less of the variation. When looking across individual workers in the United States, we find that industry mix, population density and lockdown severity help account for current WFH rates, as does the partisan leaning of the county in which the worker resides. We conclude that multiple factors influence WFH rates, and technological feasibility is only one of them.
Keywords: 330